Appetite Suppressing Activity of Rumex Usambarensis Leaf and Stem Aqueous Extract in Wistar Albino Female Rats: an in vivo Experimental Study - Atwiine, Fredrick; Mwesigwa, Albert; Mwesiga, Derick; Mwesigwa, Polly; Katumba, Lawrence; Ogwang, Patrick Engeu (Journal of Experimental Pharmacology, 2024)
Background: The burden of obesity and overweight associated morbidity and mortality is increasing in epidemic proportions worldwide. Suppression of appetite is one of the mechanisms that has been shown to reduce weight. Most of the drugs on the market currently for appetite suppression are not readily available or affordable in resource-limited settings. Additionally, previous studies have shown that most of these drugs are associated with significant adverse effects, which demonstrates a need for alternative or complementary options of drugs for appetite suppression. In Uganda, herdsmen commonly chew the raw stems and leaves of Rumex usambarensis, a wild shrub, and this is believed to reduce hunger. This study aimed at determining the effect of Rumex usambarensis aqueous extract on food intake as a measure of appetite in Wistar albino rats. Methods: This study was carried out in two phases: the fattening phase and the treatment phase. Female albino Wistar rats were fed a high-fat diet for 49 days. The fattened animals were then randomly separated into 4 groups, which received 1 mL of distilled water (negative control), 500 mg/kg body weight of aqueous extract of Rumex usambarensis, 1000 mg/kg body weight of the extract and 20 mg/kg body weight topiramate (positive control), respectively. Food intake was measured every day, and weights were taken every two days for every group. Results: Rumex usambarensis extract significantly reduced body weight of fattened rats compared to the control group at both doses: for the 500mg/kg dose (Mean difference, MD = 17.2, p < 0.001) and for 1000mg/kg dose (MD = 25.9, p < 0.001). Additionally, both doses of the aqueous extract showed a significant reduction in food intake: for the 500mg/kg dose (MD = 16.1, p < 0.001) and for the 1000mg/kg dose (MD = 37.3, p < 0.001). There was a strong correlation between food intake and weight for both doses for the 500mg/ kg dose (r = 0.744, p = 0.009), and the strongest association observed with 1000mg/kg dose (r = 0.906, p < 0.001). Conclusion: The aqueous extract of the leaves and stems of Rumex usambarensis has appetite suppressing and weight reduction effects in fattened female Wistar albino rats and could be an efficacious alternative medicine for management of overweight, obesity and other related disorders.
Keywords: Rumex usambarensis; Appetite; Weight; Obesity; Dammer